SOME ASPECTS OF PROFESSIONAL COMPETENCE FORMATION - Hojiyeva, Minovvarkhan Akramovna; Meliqo‘ziyeva , Husnidaxon Mahmudjon qizi (Educational Research in Universal Sciences, 2023)
This article provides information on competence, competence, lingvuistic competence.